Identification of novel estrogen receptor (ER) agonists that have additional and complementary anti-cancer activities via ER-independent mechanism. Issue 7 (1st April 2016) - Kim, Taelim; Kim, Hye-In; An, Ji-Young; Lee, Jun; Lee, Na-Rae; Heo, Jinyuk; Kim, Ji-Eun; Yu, Jihyun; Lee, Yong Sup; Inn, Kyung-Soo; Kim, Nam-Jung
Graphical abstract: Abstract: In this study, a series of bis(4-hydroxy)benzophenone oxime ether derivatives such as12c, 12e and12h were identified as novel estrogen receptor (ER) agonists that have additional and complementary anti-proliferative activities via ER-independent mechanism in cancer cells. These compounds are expected to overcome the therapeutic limitation of existing ER agonists such as estradiol and tamoxifen, which have been known to induce the proliferation of cancer cells.